Impact of Wire Selection on the Performance of an Induction Motor for Automotive Applications - Lino Di Leonardo; Giuseppe Fabri; Andrea Credo; Marco Tursini; Marco Villani (Energies, 2022)
This paper investigates the impact of the wire selection on the performance of induction motors for automotive applications. The section of wire and the material are evaluated at a high speed of 200 kW in an induction motor designed for premium vehicle applications. The proposed solutions have the same electromagnetic and thermal constraints, as well as the same final encumbrance. The various wire and winding types differ in terms of slot design, phase resistance, end-winding overhanging portion, skin and proximity effects, and equivalent slot thermal conductivity. Their impacts are analyzed in terms of the operating area motor efficiency and they are tested in an automotive drive cycle, highlighting the advantages and disadvantages of each configuration.